Perceptions of Teachers on National Educational Policy 2020 - Sowmya, M; Raju, D Thammi; Akhila, K; Vinayagam, S Senthil (JOURNAL OF INDIAN EDUCATION, 2022)
Formulation and implementation of policies are two different aspects that contribute to the overall achievement. The New Educational Policy (NEP) developed over time by engaging different stakeholders requires feedback from actual implementers at the grassroot level to ensure effective implementation in letter and spirit. The data on perceptions of 50 school teachers focused on three important areas–philosophical, curricular, and teachers’ aspects apart from awareness of principles of NEP, 2020. Various statistical tools are utilised for meaningful interpretation of findings such as descriptive statistics, ‘Pearson’s Correlation Coefficient, ‘Wilcoxon Signed-Rank’, ‘Man Whitney U, ‘Kruskal Wallis H’, t-test etc. The awareness of the fundamental principles of NEP was ranging from 44 per cent. The majority of school teachers were in the medium category of perception on philosophical (64.0 per cent), curricular (66 per cent), and teachers aspects (80 per cent) of National Educational Policy. The changes in teachers’ perceptions on New Educational Policy 2020 analysed the possible constraint in the implementation of NEP was discussed and appropriate strategies suggested.